Принципи систематизації законодавства про органи охорони правопорядку - Качинська, М. О.; Kachynska, M. O.; ORCID: http://orcid.org/0000-0002-7319-4470 (Право і безпека. – 2014. - № 4 (55). – С. 51-54, 2014)
Обґрунтовано необхідність систематизації законодавства про органи охорони правопорядку. Відокремлено та деталізовано принципи систематизації законодавства про органи охорони правопорядку. Звернуто увагу на виникнення нових функцій органів охорони правопорядку, у зв’язку з чим запропоновано впровадження засади «служіння інтересам людини і громадянина».

Development of Ukraine as a democratic and legal state reorganizes and refocuses the efficiency and quality of activities of the state bodies. This process concerns also legislation on reorganization of law enforcement agencies adopted by the Verkhovna Rada of Ukraine (the Ukrainian Parliament), the Cabinet of Ministers of Ukraine, the President of Ukraine and other authorized bodies. Legislation is a routine activity which leads to adoption of various legal acts and it is hard to apply them effectively. A proper systematization of law enforcement agencies legislation will improve the activities of these agencies. In such a way it demonstrates the relevance of the chosen topic. The article deals with systematization of law enforcement agencies legislation. The factors which influence on their establishment have been identified. Special attention has been given to new functions of law enforcement agencies which contribute in turn to arising of new principles. The author has proposed such principle as «serving the interests of the person and citizen». The essence of this principle is not only to enshrine the priority of these rights in legal acts but also to observe and uphold them duly and consistently. The article focuses on such social phenomenon as «telephone rule» or «white-collar crime». These concepts show illegal corruption activities at the highest authorities, law enforcement agencies etc. Various factors caused this phenomenon. They are breakup of the Soviet system and establishment of new social ideas in post-communist society. The author separates and specificates the principles of systematization of law enforcement agencies legislation. They are legality, democracy, protection and observance of human rights and legitimate interests, neutrality, scientificity, planning. Their due observance and improvement is a key element for European integration processes in Ukrainian society.

Обоснована необходимость систематизации законодательства об органах охраны правопорядка. Обособлены и детализированы принципы систематизации законодательства об органах охраны правопорядка. Обращено внимание на возникновение новых функций органов охраны правопорядка, в связи с чем предложено внедрение положения «служение интересам человека и гражданина».
The principles of systematization of law enforcement agencies legislation
Принципы систематизации законодательства об органах охраны правопорядка
Качинська, М. О. Принципи систематизації законодавства про органи охорони правопорядку / М. О. Качинська // Право і безпека. – 2014. - № 4 (55). – С. 51-54.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; систематизація законодавства; органи охорони правопорядку; правоохоронні органи; systematization of legislation; law enforcement agencies; систематизация законодательства; органы охраны правопорядка; правоохранительные органы